2022
DOI: 10.1542/peds.2021-050534
|View full text |Cite
|
Sign up to set email alerts
|

Home Health Care Utilization in Children With Medicaid

Abstract: BACKGROUND: Although many children with medical complexity (CMC) use home health care (HHC), little is known about all pediatric HHC utilizers. Our objective was to assess characteristics of pediatric HHC recipients, providers, and payments. METHODS: We conducted a retrospective analysis of 5 209 525 children age 0-to-17 years enrolled Medicaid in the 2016 IBM Watson MarketScan Medicaid Database. HHC utilizers had ≥ 1 HHC cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In terms of international comparison, the male-to-female ratio (53.7:46.3) was comparable with previous similar studies from the USA, where children used home healthcare in the Medicaid cohort (54.5:45.5) 3 and Canada, where children in Ontario with medical complexity had a ratio of 55.4:44.6. 2 From the available data, we found that (1) the crude incidence rate of children receiving home mechanical ventilation in Japan (4.1 per 100 000 children; online supplemental eTable 1 ) was higher than that in Canada (2.9 per 100 000 children) and (2) there was an increasing trend of these children in both Canada and Japan.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In terms of international comparison, the male-to-female ratio (53.7:46.3) was comparable with previous similar studies from the USA, where children used home healthcare in the Medicaid cohort (54.5:45.5) 3 and Canada, where children in Ontario with medical complexity had a ratio of 55.4:44.6. 2 From the available data, we found that (1) the crude incidence rate of children receiving home mechanical ventilation in Japan (4.1 per 100 000 children; online supplemental eTable 1 ) was higher than that in Canada (2.9 per 100 000 children) and (2) there was an increasing trend of these children in both Canada and Japan.…”
Section: Discussionsupporting
confidence: 85%
“…Recent efforts have attempted to reveal important information regarding CMC from various perspectives, including home healthcare use, 3 evaluation of care coordination/programmes 4 5 , medication safety 6 and their caregivers. 7 8 However, evidence remains inadequate for these children, especially children receiving home healthcare devices (HHDs).…”
Section: Introductionmentioning
confidence: 99%
“…Frameworks used to define medical complexity for children include severity and number of complex chronic conditions, functional limitations, and health-care needs among other factors (Berry, Agrawal, et al, 2011). Addressing the multifaceted needs of these medically high-risk children entails frequent care from a spectrum of primary and subspecialty providers, in addition to at-home care (Perrin, 2002; Sobotka et al, 2022).…”
mentioning
confidence: 99%